Clinical and laboratory comparison of severe (Group B and C) Dengue cases with molecular characterization from 2019 epidemics in Dhaka, Bangladesh. - Fazle Rabbi Chowdhury; Zazeba Hossain; Nahid Parvez; Forhad Uddin Hasan Chowdhury; Mohammad Anwarul Bari; Sudip Ranjan Deb; Mustak Ibn Ayub; Md Uzzwal Mallik; Sakib Aman; Mohammad Ahsanul Haque; Md Arman Hossain; Murada Alam; et al. (PLoS Neglected Tropical Diseases, 2024)
Acute arboviral infections like dengue have a significant negative socioeconomic and health impact on many tropical and subtropical areas of the world. About 3.9 billion Individuals are at risk of contracting the dengue virus and Asia bears the brunt of that load. Bangladesh, like other south-east Asian countries faced a massive outbreak of dengue in 2019. This cross sectional study was done in three tertiary care centers in Dhaka, Bangladesh during this worst outbreak of dengue. The study was conducted from 1st July to 31st December, 2019 with an aim to describe the clinical and laboratory variations among severe dengue cases and to conduct a serotype survey. This might help to understand the future changes in the clinical or serological profile of the circulating dengue virus. The study enrolled 1978 participants who were grouped into group B (Patients with warning signs or risk factors who should be admitted for close observation as they approach critical phase) and C (Patients having severe plasma leakage leading to dengue shock and/or fluid accumulation with respiratory distress, severe organ impairment and severe metabolic abnormalities) according to national guidelines. Furthermore, 81 samples were serotyped using Qiagen One step RT-PCR kit (Cat. No: 210212). In addition sequencing (ABI sequencing platform) of partial C-prM gene of five DENV-3 isolates were done and analyzed (BLAST tool of NCBI) for phylogenetics (MEGA6 software package). Among the 1978 enrolled participants group B and C patients were 1580 (80%) and 398 (20%) respectively. The median (IQR) age of the patients were 26(11 to 41). Maximum proportion of the enrolled were male (72.3%) (p = 0.0002). Most common co- morbidities were hypertension (90; 4.5%) and DM (70; 3.5%). Group C patients more commonly presented with vomiting (p 0.133), diarrhea (p<0.0001) and abdominal pain (p 0.0203). The common mode of bleeding was melaena (12%). Thirteen (0.7%) patients succumbed to death, 12 of them belonged to group B who mostly presented with GI manifestations (99.9%) and melaena (12%). Only 5.6% of the cases were secondarily infected. In group C cases low hemoglobin and hematocrit was observed with high AST (p 0.004, 0.006 and 0.0016 respectively). Fluid requirement was also more in the same group (p<0.0001). Group B patients had a higher platelet requirement (p = 0.0070). Twelve patients (0.7%) required ICU. The management profile of these cases are showcased here which highlights minimal use of antibiotics and no application of steroids, which abides by the current national protocol. Furthermore, 81 samples from enrolled participants were serotyped and majority (79%) yielded DENV-3, followed by DENV 2 & 3 co-infection (13.6%) and DENV-2 alone (7.4%). Following phylogenetic analysis DENV-3 and DENV2 were deemed to be of genotype I and cosmopolitan variety respectively. This study presents the first instance of heterogeneous co-infection with several serotypes since 2000 in Bangladesh. It also gives an overview of serotype prevalence, management evaluation and clinical results that promises to navigate future control planning.